Jérôme: Trois vies de moines. Paul, Malchus, Hilarion. Critical text by Edgardo M. Morales. Translated by Pierre Leclerc - Winterbottom, Michael (The journal of theological studies, 2008)
This welcome new volume of Sources chrétiennes provides under one cover new editions of Jerome's saints’ Lives, two of them based on the doctoral theses of R. Degòrski (Paul) and E. M. Morales (Malchus). These short works, dating to the fifteen years from 376, were written in the east, and the wild desert leaves its mark on them. Together with Athanasius’ Life of Antony, influentially translated by Evagrius, they mark the beginning of Latin hagiography. The three saints, all dating to the fourth century, hailed from Egypt, Palestine, and Syria, and stood for three different emphases in engagement with the solitary life. Scholars have found it irresistible to look for some elements of autobiography in Jerome's little books.